PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK DALAM MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV - Rahmah, Fauziah (Transpublika Publisher, 2024)
The concern about the low learning outcomes of students in class lV SDN lV Karangampel Kidul in science subjects due to students' lack of interest in science subjects is the background for this research. One of the efforts made is the application of a project-based learning model. This study aims to determine the application of project-based learning models in science subjects for grade IV students of SDN IV Karangampel Kidul, Karangampel District and to determine the application of project-based learning models can improve the learning outcomes of grade IV students of SDN IV Karangampel Kidul, Karangampel District. This research used PTK (class action research) method with Kemis and Taggart design. The research sample was all fourth grade students of SDN lV Karangampel Kidul in the 2022/2023 school year, totaling 31 students. By using data collection techniques in the form of interviews, observations and tests. Based on the observation results in this study, it is included in the good category, seen from the analysis of teacher activity observation data in cycle I obtained 75% with sufficient criteria and increased in cycle II 87.5% with good criteria. And student learning outcomes are said to have increased, this can be seen from the results of student learning in cycle I which has been completed 74.19% and increased in cycle II, namely 83.87% of students who have been completed and can be said to have reached the success indicator of 80%.